PERAN NET INTEREST MARGIN (NIM) DALAM MEMPERKUAT PENGARUH LOAN TO DEPOSIT RATIO (LDR) TERHADAP PERUBAHAN LABA PADA BANK DEVISA DI INDONESIA - Astohar . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
Changes in banking profits in the referene to find business prospects in the future. Loan to deposit ratio is a variable that is unique in affecting change in earnings. The uniqueness of the results of different studies show, that there was a significant positive effect or which have significant negative effects. Net interest margin included in the study to reinforce the influence loan to deposit ratio to changes in earnings. The study was conducted on a Devisa bank registered in Indonesian Bank 2006-2009 period by taking a sample of 26 foreign banks. Data collection methods used are literature and documentation. Analysis of data using techniques of data normality test, the deviation of classical assumptions, test moderation regression analysis, and hypothesis testing using the SPSS. The results showed that the Loan to Deposit Ratio did not prove a negative and significant impact on profit of changes in foreign exchange bank in Indonesia. Net interest variables can not strengthen the influence of a variable loan to deposit ratio to changes in earnings on bank foreign exchange bank in Indonesia.